2015
DOI: 10.1007/s10067-015-3155-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of impaired quality of life in patients with rheumatic diseases

Abstract: Quality of life (QoL) is a complex outcome and rheumatologic patients typically exhibit several comorbidities with a negative impact. In this study, we analyzed with respect to QoL for the first time a wide range of physical and psychological factors, including individual, clinical and disease-related parameters, mental health disorders, sexual dysfunction, and cardiovascular comorbidities among consecutive rheumatologic patients. QoL was evaluated using the EuroQol 5D (EQ-5D) utility index. The Health Assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 31 publications
2
24
0
4
Order By: Relevance
“…This was also found using the EuroQol 5D (EQ-5D) utility index in a recent study on patients with different rheumatic diseases from rheumatology outpatient clinics. 13 Several studies have described a poorer response to pharmacological treatments of females than males with RA 14 , 15 or SpA. 16 , 17 Similarly, male gender has been found to be predictive for both response (BASDAI 50, ASAS 20, and ASAS 40) and treatment continuation in ax-SpA.…”
Section: Discussionmentioning
confidence: 98%
“…This was also found using the EuroQol 5D (EQ-5D) utility index in a recent study on patients with different rheumatic diseases from rheumatology outpatient clinics. 13 Several studies have described a poorer response to pharmacological treatments of females than males with RA 14 , 15 or SpA. 16 , 17 Similarly, male gender has been found to be predictive for both response (BASDAI 50, ASAS 20, and ASAS 40) and treatment continuation in ax-SpA.…”
Section: Discussionmentioning
confidence: 98%
“…The impact of the disease on HRQoL is comparable to other diseases. In arthritis, a number of studies have demonstrated significantly lower quality of life compared to the general population both in patients with rheumatoid arthritis [33][34][35][36][37] and in those with psoriatic arthritis [38][39][40][41] . This underlines the need for new treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Anyfanti, dkk. 20 melakukan penelitian terhadap 360 pasien penderita penyakit reumatik yang juga memiliki penyakit kronik lainnya. Dari penelitian tersebut didapati bahwa beberapa penyakit kronik, yaitu diabetes melitus dan hipertensi, juga memengaruhi kualitas hidup, sehingga penafsiran hasil penilaian kualitas hidup pasien yang memiliki lebih dari satu penyakit kronik dengan menggunakan instrumen generik perlu dilakukan dengan lebih hati-hati.…”
Section: Pendahuluanunclassified